Outdoor Communities in Iluminación artificial, by Cristofer Vargas Cayul - María Fernanda Libro (Estudios de Teoría Literaria)
This article discusses the novel Iluminación artificial (2021), by first-time writer Cristofer Vargas Cayul (Santiago, 1993). Part of a generation of writers who spent their childhood during the radicalisation of neoliberal policies in Chile in the 1990s, Vargas Cayul's novel is set in the suburban periphery of Santiago - that liminal zone where diverse populations, deterritorialised from their communities of origin, converge - overshadowed by the apocalyptic atmosphere of the end of the millennium. A space common to some contemporary Mapuche writing (Aniñir; Milanca Olivares; Catrileo, 2021 and 2024; Coñuecar; Huenún, 2001 and 2012), the “toma” represents the final destiny both for those subjectivities expelled from national citizenship and for Mapuche subjectivities banned from the ancestral community - the lof. This paper investigates the modes of grouping that Vargas Cayul's work proposes on the basis of the forced displacements staged in his novel: the question that emerges in this enquiry is what kind of community the subjectivities represented therein make up, once their original communities (be they ethnicity, class or nation) no longer contain them. The article thus takes up theoretical problematisations addressed in previous works in relation to Mapuche writing (Libro, 2019, 2021, 2024), linking them now to a novel that does not necessarily fit in with what specialised critics include in this nominal construct.